Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-33 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Ten-year-old patient with an incomplete spinal cord injury at the Th10 level during creeping. Note, because of the severe scoliosis, the creeping is not symmetrical. The rotation to the left is limited because of the scoliosis. C. Training of right-left symmetry via the corpus callosum (D) when exercising on the special CDT device with crossed arms.